2015
DOI: 10.1097/bot.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Reduction Loss in Proximal Humerus Fracture Surgery

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 25 publications
3
80
2
3
Order By: Relevance
“…Medial support was proven to be an important factor for a good functional outcome in other studies 13, 19. Jung et al reported only 1% patients had loss of reduction with adequate medial support in their serials 13 . In this study, the authors held a low threshold for structural allograft augmentation.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Medial support was proven to be an important factor for a good functional outcome in other studies 13, 19. Jung et al reported only 1% patients had loss of reduction with adequate medial support in their serials 13 . In this study, the authors held a low threshold for structural allograft augmentation.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, calcar screws were routinely placed closed to inferior cortex of humeral head in our practice. Medial support was proven to be an important factor for a good functional outcome in other studies 13, 19. Jung et al reported only 1% patients had loss of reduction with adequate medial support in their serials 13 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many studies have considered that medial support in proximal humerus fracture surgery is crucial to avoid reduction loss and varus displacement. Jung et al [18] revealed that insu cient medial support was an independent risk factor for reduction loss in proximal humerus fractures (p < 0.01). Maier et al [19] also found that short or absent metaphyseal head extension and disruption of medial periosteal hinge reliably predict posttraumatic humeral head ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several parameters, such as varus displacement or medial comminution, were significantly correlated with reduction loss [10, 42], but more specific parameters are needed to detect postoperative failures early.…”
Section: Discussionmentioning
confidence: 99%